Road to ruin - Laurance, William (Himalayan Journal of Sciences, 2008)
Tough laws won’t save poor nation’s ecosystems until the impacts of developments are taken seriouslyReprinted with permission from New Scientist, issue 2607, 06 June 2007, page 25Himalayan Journal of Sciences Vol.4(6) 2007 p.9